A verdade em tempos de ditadura militar: reflexões a partir da psicanálise - Nadir Lara Junior (Ciências Sociais Unisinos)
The aim of this article is to reflect about how the truth assumed by the military and their followers becomes an ideological fantasy in which they justify their actions and beliefs. They intend to turn the truth of the violence and horror of torture into something mild and negligible. For this purpose, we use psychoanalytical theory, which helps us to understand the system of oppression introduced during the military dictatorship in Brazil, as well as the contemporary discursive construction that presents that regime as a "ditabranda" (a Portuguese play on words that roughly means "a soft dictatorship"). This theory also enables us to think about how the subjects who participated in this ideological fantasy must be held accountable for their violent acts, even if they insist on not wanting to know about them.